Coal Price and Profitability: Evidence of Coal Mining Companies in Indonesia - Endri, Endri; Utama, Andyan Pradipta; Aminudin, Aminudin; Effendi, Maya Syafriana; Santoso, Bambang; Bahiramsyah, Achmad (International Journal of Energy Economics and Policy, 2021)
The study examines the influence of certain industrial factors, namely the reference price for Indonesian coal (HBA), and internal factors, namely; debt to equity ratio (DER), growth, current asset (CR), and company size (size) to profitability (ROA) of coal companies Indonesia during 2015-2019. The study population was all coal companies listed on the IDX before 2015. By using a purposive sampling technique, 13 companies were obtained. The research variable data was estimated using the Panel data method. The results show that DER adversely affects ROA, and company growth is in line with the increase in ROA. HBA and CR variables do not affect ROA. The implication of the research results is to increase profitability, the company to increase sales through business diversification other than coal products, and reduce the total debt held so that it does not become a heavy payment burden. Keywords: Coal Price, Profitability, Coal Mining Companies, Indonesia JEL Classifications: G11, G30, G32, Q31 DOI: https://doi.org/10.32479/ijeep.11503